Characterization of the vegetation cover and water erosion dynamics in the Aghien lagoon catchment - Koffi, Serge Ehouman; Dao, Amidou; Noufe, Dabissi Djibril; Ouedraogo, Mamadi; Yeo, Nagnon Bernard; Seguis, Luc; Perrin, Jean Louis; Kamagate, Bamory; Gone, Lancine Droh (European Scientific Journal, ESJ, 2024)
Soil erosion affects land quality and water resources. The present research aimed to estimate spatio-temporal changes in land-use/land-cover pattern and soil erosion in the lagoon Aghien watershed in Côte d’Ivoire. This study was carried out by using Landsat imageries of 2016 and 2020. Images were classified into categories using supervised classification by the maximum likelihood algorithm. Universal Soil Loss Equation modeling was applied in a GIS environment to quantify the potential soil erosion risk. The area of bare soil/Habitats and crops/Fallow increased by 2981 ha (37.8%) and 2642 ha (17.58%) during 2016–2020. The high soil losses are located on the slopes of the rivers and valleys adjacent to the Aghien lagoon, which are also naturally favored by the steepness of the slopes and their length and inclination. However, the average soil loss values were 60.65% in 2016 and 47.64% in 2020. However, the very low and low soil loss values are scattered over the watershed for an area of 34441.52 ha corresponding to a rate of 94.36% in 2016, in 2020 they occupy an area of 34956.76 ha with a rate of 95.77%. On the other hand, high and very high soil losses are insignificant, corresponding to rates of 0.95% and 0.60% in 2016 and 2020 respectively. However, most of the soil loss in the watershed is due to moderate erosion, occupying areas of 1712.19 ha (4.69%) and 1305.77 ha (3.58%) also in 2016 and 2020.